Homoeopathic Medicine Industry in India: Covid 19 Challenges and the Road Ahead (Homoeopathy for All, 2022)
There are so many challenges the industry faces today. Though challenges are not new for homoeopathy, current challenges are a hindrance for the homoeopathic industry to sustain and accelerate its growth, especially in the Post COVID 19 scenario. COVID 19 has brought challenges in both positive and negative aspects. Along with the limitations it brought, it helped the industry to realize that it can handle any such difficult situation, as we all have learnt in our personal life. From a mid-single-digit growth, COVID 19 has brought up higher double-digit growth. There is positive momentum felt across the industry. Arsenicum album has become a household name, thanks to the Ayush Ministry. It took the name of homoeopathy to each and every home in the country. It facilitated a much stronger penetration of homoeopathy across geographical market segments. Current growth is the highest ever in recent times. Now the challenge is how to sustain this growth momentum. Though it is a sweet challenge, it needs coordinated efforts to make and execute strategies to sustain this.This article focuses on the challenges brought in by COVID 19 and also the road ahead to move forward.
Keywords: COVID 19; strategies